ANALISIS TINGKAT PELAYANAN PASIEN POLIKLINIK RUMAH SAKIT ABDUL RIVAI DI KABUPATEN BERAU - Maya Dasia (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
The aim of the study was to determine the quality of service provided by Abdul Rivai hospital in District Berau. The benefit of the research is as an input for Abdul Rival hospital to maintain the quality of service. In this study, the assessment of service quality is divided into five categories: Manners of employees, employee communication ability, speed of service, hospital facilities, and employee performance. All categories show that consumer’s perception of services provided by hospital has been quite satisfactory. The calculation of average weighted values for the five categories used are manners of employees, employee communication ability, speed of service, hospital facilities, and employee performance are 3,126